Large-scale analyses of schizophrenia proteome (Archives of Clinical Psychiatry, 2013)
Valuable knowledge about schizophrenia has been recently generated for deciphering its pathobiology and revealing biomarkers. However, efforts are still needed, especially if we take in account that this debilitating mental disorder affects approximately 30 million people worldwide. Considering that schizophrenia is a result of a complex interaction among environmental factors altered gene function and systematic differential protein expression, proteomics is likely to be a suitable tool for studying this disorder. Here we synthetize the main findings by proteomic studies and further directions to be taken in order to better comprehend the biochemistry of schizophrenia as well as reveal biomarkers. In addition, we summarize proteomic methodologies used in such studies.